2016
DOI: 10.1016/j.chb.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

How gender role stereotypes affect attraction in an online dating scenario

Abstract: Today, it is not uncommon to meet someone and begin a romantic relationship on the internet. Meeting on a dating website differs from meeting in person because a dating profile is created first that allows others to review potential romantic partners. Few studies have examined romantic attraction within an online dating context, and even fewer have examined how gender roles may influence attraction. Two studies were conducted. Study 1 (N = 447, 49.4% female) examined the effects of gender role congruence and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 51 publications
(61 reference statements)
2
25
1
1
Order By: Relevance
“…A componente visual, contrariamente à componente escrita, ajuda mais rapidamente na criação de uma impressão e ao contrário dos textos contribui significativamente para atrair potenciais parceiros (De Vries, 2007). Estudos anteriores, como (Cash el al.., 2004;Humphreys, 2006;Siibak, 2009;De Vries, 2010;Toma & Hancok, 2012, Casimiro, 2015Chappetta, 2016, Miguel 2016) demonstraram não apenas importância das fotografias, assim como deste tipo de autoapresentação, e encontraram diferenças entre géneros e idades. Figura 1: Percentagem de fotos identificáveis versus não identificáveis -n = 701…”
Section: As Fotografias -A Componente Visualunclassified
“…A componente visual, contrariamente à componente escrita, ajuda mais rapidamente na criação de uma impressão e ao contrário dos textos contribui significativamente para atrair potenciais parceiros (De Vries, 2007). Estudos anteriores, como (Cash el al.., 2004;Humphreys, 2006;Siibak, 2009;De Vries, 2010;Toma & Hancok, 2012, Casimiro, 2015Chappetta, 2016, Miguel 2016) demonstraram não apenas importância das fotografias, assim como deste tipo de autoapresentação, e encontraram diferenças entre géneros e idades. Figura 1: Percentagem de fotos identificáveis versus não identificáveis -n = 701…”
Section: As Fotografias -A Componente Visualunclassified
“…Thus, although some studies have highlighted the role of photos and physical characteristics (Morgan et al, 2010;Bak, 2010;Chappetta & Barth, 2016), other factors are also shown to be relevant such as personality (Morgan et al, 2010) ) ), an authentic or warm nature that inspires confidence and appears extroverted in the case of men, or appearing feminine with high self-esteem and not narcissistic in the case of women (Fiore et al, 2008). The significant differences between the results obtained in different researches could be related to the groups selected to be studied and the specific online dating sites used as sources of information.…”
Section: Online Dating: State Of the Artmentioning
confidence: 99%
“…A more recent study of college students found that the students actually preferred gender role incongruent potential romantic partners rather than gender role congruent ones (Chappetta and Barth, 2016). In this study, mock online dating profiles were constructed that included pictures of potential dates, descriptions of their hobbies, interests, what they were looking for in a romantic partner and other personality traits.…”
Section: Role Congruity and The Effect On Mates Dating And Attractivmentioning
confidence: 98%
“…There are also conflicting results as to whether or not gender role congruence makes a person more or less attractive than gender role incongruence in previous studies based on whether the researchers are looking at gender role congruity in respect to short or long term relationships (Thomae and Houston, 2015;Chappetta and Barth, 2016). In order to address this issue, levels of attraction towards gender role congruent and incongruent individuals in the context of both short and long term relationships will be examined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation